Adjacent Segment Degeneration after Short-Segment Lateral Lumbar Interbody Fusion (LLIF). (24th March 2022) - Ouchida, Jun; Nakashima, Hiroaki; Kanemura, Tokumi; Matsubara, Yuji; Satake, Kotaro; Muramoto, Akio; Ito, Kenyu; Tsushima, Mikito; Morozumi, Masayoshi; Segi, Naoki; Morita, Yoshinori; Imagama, Shiro
Abstract : Purpose. To investigate the influence on the adjacent segment degeneration (ASD) of short-segment lateral lumbar interbody fusion (LLIF) at 2 years postoperatively. Methods. Ninety-seven consecutive patients who underwent one- or two-level LLIF were included from two institutions. We diagnosed radiographical adjacent segment degeneration with the appearance of adjacent spondylolisthesis (>3 mm) or deterioration of adjacent disk height (>3 mm) on plain radiographs or decrease of the intervertebral angle (>5 degrees). The differences between the two groups with and without radiographical ASD were investigated using univariate and multivariate analyses to determine the risk factors for ASD. The variables included extent of adjacent decompression, posterior fixation method (open method or percutaneous method), and facet violation on postoperative CT. Results . In total, 19 patients (19.6%) were diagnosed as radiographical ASD 2 years after surgery. Univariate analysis showed that the ASD (+) group had a high frequency of adjacent decompression (21.1 vs. 3.8%, p = 0.035 ) compared with the ASD (-) group. There were no differences between the two groups in posterior fusion method (percutaneous method 42.1 vs. 57.7%, p = 0.221 ) or facet joint violation (15.8 vs. 14.1%, p = 0.860 ). The multivariate analysis found adjacent intervertebral decompression to be a risk factor for ASD 2 years after surgery (odds ratio: 9.95; 95% confidence interval: 1.2–82.1). Conclusions. Adjacent intervertebral decompression was considered to be a potential risk factor for the development of ASD after spinal fusion with LLIF.